2015
DOI: 10.1177/1534734615580017
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Serum Triglycerides Were Associated With Postoperative Deep Vein Thrombosis After Total Hip Arthroplasty in Patients With Nontraumatic Osteonecrosis of the Femoral Head

Abstract: This retrospective study aimed to evaluate the association of serum lipids and deep vein thrombosis (DVT) risk following total hip arthroplasty (THA) in patients with nontraumatic osteonecrosis of the femoral head (ONFH). A total of 224 nontraumatic ONFH patients were enrolled. Serum levels of triglycerides (TG), total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol were detected preoperatively. All the patients underwent unilateral lower extremity venography on posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
7
1
3
Order By: Relevance
“…Regarding the pathogenic mechanism of AVNFH induced by the dysregulation of lipid metabolism, the present study suggested that on the one hand, hyperlipidaemia damages vascular endothelial cells to create pro-thrombotic conditions: the ability of vascular endothelial cells to synthesize nitric oxide (NO) decreases resulting in the dysfunction of vascular contraction and relaxation, which affects bone microcirculation [ 13 , 18 , 22 ]. On the other hand, hyperlipidaemia leads to the formation of fat emboli in the peripheral blood, causing bone microvascular obstructions, increasing the intraosseous pressure, and further aggravating the dysfunction of bone microcirculation [ 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the pathogenic mechanism of AVNFH induced by the dysregulation of lipid metabolism, the present study suggested that on the one hand, hyperlipidaemia damages vascular endothelial cells to create pro-thrombotic conditions: the ability of vascular endothelial cells to synthesize nitric oxide (NO) decreases resulting in the dysfunction of vascular contraction and relaxation, which affects bone microcirculation [ 13 , 18 , 22 ]. On the other hand, hyperlipidaemia leads to the formation of fat emboli in the peripheral blood, causing bone microvascular obstructions, increasing the intraosseous pressure, and further aggravating the dysfunction of bone microcirculation [ 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adipocyte hypertrophy, fat accumulation, and fatty marrow in the femoral head increases bone marrow microcirculation pressure, which contributes to the ischaemia, hypoxia, metabolic disorders, and edema observed in bone marrow tissue, resulting in secondary intracranial pressure increases and further aggravating ischaemia and hypoxia. This creates a vicious cycle, eventually resulting in consequences such as bone dystrophy or bone necrosis [ 10 , 13 , 24 ]. Increased blood viscosity, decreased erythrocyte deformability, and microcirculation congestion also damages the blood supply to the femoral neck fracture site after surgery, which contributes to the relative ease of the development of ischaemic necrosis of the femoral head [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary osteonecrosis of the femoral head is due to gene or gene mutation of patients. Secondary osteonecrosis of the femoral head could divide into traumatic and nontraumatic osteonecrosis of femoral head [ 6 – 8 ], in which traumatic osteonecrosis of the femoral head is the avascular necrosis of osteocyte caused by interruption of blood flow in the blood vessels in femoral head, which was due to trauma [ 9 , 10 ]. Its etiology is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Primary ANFH is predominately associated with specific genes in patients or due to gene mutation, whereas secondary ANFH includes traumatic and non-traumatic ANFH ( 6 – 8 ). It is well known that the etiology of traumatic ANFH is caused by the interruption of blood flow in blood vessels of the femoral head ( 9 , 10 ). In previous years, with the widespread clinical use of corticosteroids, cases of femoral head necrosis have increased substantially ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%